Beta-Glucanas extraídas do fungo Caripia montagnei (Berk.) Kuntze: uma análise das suas propriedades antioxidante, antitumoral, antiangiogênica e anti-inflamatória de forma isolada e em sinergia com AINEs, L-NAME e ligantes de PPAR alfa e gama - Castro, Allisson Jhonatan Gomes (2011)
Glucans are homopolymers of D-glucose with bioactive properties with direct influence o activation of leukocytes and antitumoral, antioxidant and immunomodulatory activities. The aim of, this paper was to verify the efect of p-glucans extracted from the mushroom Canpia m 9 the inhibition of the inflammation, angiogenesis and free radicais. The fraction polysaccna showed carbohydrate (98.5%), protein (1.5%) and 0.1 mg / mg of phenolic compounds. Its monosaccharide composition showed predominantly glucose by means of HPLC, with nuclear magnetic resonance (nmr) confirmed the presence of D-glucose to 103.5 ppm in P configuratio. The viability of fibroblasts in the presence of glucans from C. Montagnei at 25 uq was 83.3±17,6%, with high cytotoxicity on tumoral cells (HeLa) at 100 ug (94.36±2.3%). The anti-edematous activity observed at 90 mg/kg of Carípia montagnei was 90.7 ± 3.5%. The synergy with parecoxib showed was 81 3+7.4%, 100±12% to L-NAME and 97.8+10% with PFOA. In study made with carrageenan 91.043±7,3%. The production of nitric oxide with Caripia polysacchandes was (48.2%) was better than the activity of indomethacin. The glucans of C. montagnei showed significant antiangioge activity with 1 mg/egg (p>0.05). In total antioxidant activity and reducmg power was foundI for the relative antioxidant activity of BHT 57% and 84%, respectively. The evaluation of the inhibition of hydroxyl radical (1 mg/ml) was 38±0.01%, while for the lipid peroxidation was observed an inhibition of 37 6±0 16%. The present results showed that p-glucans from Carípia montagnei have inhibitory activity in these models of inflammation, angiogenesis and inhibition of free radicais.